Juan Del Valle y Caviedes on the margins of the intellectual city: «intratextuals» strategies of self-legitimation - Martín Puya, Ana Isabel (Arte Nuevo. Revista de Estudios Áureos, 2017)
In the work of Juan del Valle y Caviedes it is possible to find several recurring elements through which the author builds his public image, as part of a strategy to obtain recognition and notoriety in his close environment (space and time-wise). Our analysis of Caviedes creative strategy is based on a series of binomials derived from the thinking of Contrarreforma, prevailing in the XVII century Spain, and in line with the author's literary interests and his self-legitimating proposal. This leads to an innovative approach that enables us to identify the peculiarities of his work and enlighten the motives of the apparent inconsistency or ambiguity of his production. Through these opposed concepts the poet moves away and stands against his academic/social rivals; proceeding from a peripheral viewpoint in the Peruvian ciudad letrada (intellectual city) of the late seventeenth century, Caviedes’s self-legitimation is founded upon the elevation of his poetic genius above the material aspects of life, target and ground with which he identifies his opponents.